Age immaterial: women over 50 in the workplace - a TUC report (London, 2014)
"This report sets out the findings of the Age Immaterial project, which through labour market analysis, an online survey and specially commissioned polling gathered vital information about the challenges facing older women at work. It provides a set of policy recommendations on areas such as discrimination; the pay gap; caring and working; and health and training."